Adult Otogenic Meningitis in the Pneumococcal Conjugated Vaccines Era - Marom,Tal (2020)
Abstract Introduction Streptococcus pneumoniae is a major pathogen of otogenic meningitis (OgM), the most commonly reported intra-cranial complication of otitis media (OM). Objectives To study the changes in adult OgM patients in the pneumococcal conjugated vaccines (PCVs) era. Methods Retrospective cohort of adults presenting with concurrent OM and meningitis in a secondary medical care center between 2005 and 2015. Data collected included demographics, OM-related symptoms, cerebrospinal fluid (CSF) and ear culture results, pre- and during hospitalization antibiotic treatment, imaging findings, and complications. We compared the pre-PCV years (2005-2009) with the post-PCV years (2010-2015). Outcomes were 1) incidence of all-cause adult OgM from the total meningitis cases; 2) impact of PCVs on the clinical presentation of OgM and bacteriology. Results Otogenic meningitis was diagnosed in 26 out of 45 (58%) cases of all-cause meningitis admissions. Of those, 10 (38%) were male, with a mean age of 62.4 years old. Ear-related signs and symptoms were documented in 70% of the patients, and OgM was diagnosed following imaging studies in 6 out of 26 (23%) patients. All of the patients received intravenous antibiotic therapy, and 7 (27%) patients required surgical interventions: 6 required myringotomy and 1 required mastoidectomy. There were 12 (46%) patients in the pre-PCV years and 14 (56%) in the post-PCV years. The positive pneumococcal CSF and ear culture rates remained high and unchanged (~ 75%). There were no significant changes in the clinical presentation or mortality rates. Conclusion Micro-otoscopy should be included in the routine work-up of any suspected adult meningitis, because OgM is underdiagnosed. Unlike their impact on pediatric otitismedia, PCVs did not change the epidemiology and bacteriology of OgM.